2022
DOI: 10.1007/s00403-022-02383-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of medical service insurance claims as a surrogate for ascertaining vitiligo cases

Abstract: Background: The epidemiology of vitiligo, especially its disease burden on the healthcare system, can be assessed indirectly by analyzing health insurance claims data. Validating this approach is integral to ensuring accurate case identi cation and cohort characterization.Objectives: The primary aim of this study was to develop and validate an indirect measure of vitiligo ascertainment using health insurance claims data. These data were used secondarily to identify demographic characteristics, body site involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our analysis of the data revealed that vitiligo was diagnosed in 0.04% of the included patients with ESRD. Although the use of health insurance claims has previously been shown to demonstrate high diagnostic performance for vitiligo, it is worth noting that the lower proportion of patients identified within this population compared to national estimates may be attributable to underreporting among groups with higher prevalence (non-white) and/or due to the presentation of the disease (unilateral, segmental) [1,23].…”
Section: Discussionmentioning
confidence: 84%
“…Our analysis of the data revealed that vitiligo was diagnosed in 0.04% of the included patients with ESRD. Although the use of health insurance claims has previously been shown to demonstrate high diagnostic performance for vitiligo, it is worth noting that the lower proportion of patients identified within this population compared to national estimates may be attributable to underreporting among groups with higher prevalence (non-white) and/or due to the presentation of the disease (unilateral, segmental) [1,23].…”
Section: Discussionmentioning
confidence: 84%